Multi-stream deep learning for isolated sign language recognition in videos - Alsharif, Muhammad H., author; Anderson, Charles, advisor; Kirby, Michael, committee member; Blanchard, Nathaniel, committee member; Peterson, Christopher, committee member (Colorado State University. Libraries, 2025)
Isolated sign language recognition is the task of identifying signs performed in isolation across multiple frames in a video. Advances in this field have significant implications, such as improving visual communication between humans and machines and bridging the communication gap between deaf and hearing individuals. However, practical applications of this domain have been limited by two key challenges: the computational complexity of current models and the limited availability of training data for many vocabularies in sign languages. This dissertation addresses these challenges driven by improving recognition accuracy and computational efficiency. 3D convolutional models with RGB and optical flow inputs have been widely utilized in state-of-the-art methods for action recognition. Despite their significant computational costs, a systematic evaluation of their contribution to sign recognition has been limited. We first evaluate the effectiveness of 3D convolutional networks, showing that they significantly outperform their 2D counterparts on several sign recognition datasets, even when compared to a deeper 2D architecture. Additionally, this research challenges conventual assumptions about optical flow, demonstrating through ablation studies that its primary value lies in masking irrelevant (static) regions rather than improving the learning of motion patterns for sign recognition. In addition to RGB and optical flow, this work investigates skeleton-based sign language recognition using recurrent, transformer, and spatiotemporal convolutional graph networks. Our experimental results demonstrate the importance of the spatiotemporal sparse graph representation of skeleton data (coordinates of body and hand joints) in improving accuracy and interpretability through edge importance weighting. To address the limited number of training data for many signs, we propose a coarse-to-fine transfer learning approach to adapt spatiotemporal features learned from large action recognition and Turkish sign language datasets to American sign language datasets. This approach results in significant improvement for multiple modalities and benchmarks. To combine different models in a multi-stream network, we propose several methods for fusing the stream outputs before and after classification. To find the best combination of models using RGB, optical flow, or skeleton as input modalities, we train and evaluate all possible combinations in two- and three-stream networks on three sign recognition datasets. Our findings show that combining RGB and skeleton-based streams provides the most significant gain over the RGB baseline, due to greater diversity in stream predictions. In contrast, combining RGB and optical flow-based streams significantly increases the computational cost, due to optical flow extraction, without improving accuracy over two RGB streams. Our two- and three-stream networks, using only RGB and skeleton data as input modalities, achieve new state-of-the-art accuracy on the two largest ASL video datasets, which include 1000 and 2000 signs. Our approach achieves over 90% top-5 recognition accuracy on all benchmarks while significantly reducing computational costs compared to state-of-the-art methods. These findings facilitate real-time applications on mobile devices aimed at improving convenience in the daily lives of deaf individuals and helping to overcome communication barriers.
Keywords: deep learning; multi modal; sign language recognition; machine learning; artificial neural networks; multi stream